PLS-SEM Model of Crime Mitigation Performance of Abu Dhabi Police Predictive Policing - Al Shamsi, Hind Rashed Saleh; Safei, Suaidi (Tropical Scientific Journal, 2023)
Objective: This study aimed to develop a Structural Equation Model (SEM) using Partial Least Square (PLS) of Crime Mitigation Performance of Abu Dhabi Police Predictive Policing Research Method: The model is developed and evaluated in SmartPLS software. A total of 316 valid responses from questionnaire survey were used for developing the model. The survey was conducted amongst employees of the Abu Dhabi Crime Scene Department. The model was evaluated at measurement component and structural component of the model. Findings: It was found that at measurement component, all the evaluation criteria are achieved. Furthermore, the structural component also achieved the fitness criteria of the model. For hypothesis, it was found that there a significant connection between Collaborative Learning (CL) and Crime Mitigation Performance (CMP), with a p-value of 0.001, and Innovative Officer Performance (IOP) with an even more substantial p-value of 0.000. These factors evidently impact CMP. In contrast, Predictive Policing Adoption (PPA) and Specialised Technology Training (STT) lack statistical significance, with p-values of 0.509 and 0.972 respectively, suggesting chance-driven associations. Originality: The developed PLS-SEM model of Crime Mitigation Performance of Abu Dhabi Police Predictive Policing